2014
DOI: 10.1037/a0035465
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of staying active in old age: Physical activity counteracts the negative influence of PICALM, BIN1, and CLU risk alleles on episodic memory functioning.

Abstract: PICALM, BIN1, CLU, and APOE are top candidate genes for Alzheimer's disease, and they influence episodic memory performance in old age. Physical activity, however, has been shown to protect against age-related decline and counteract genetic influences on cognition. The aims of this study were to assess whether (a) a genetic risk constellation of PICALM, BIN1, and CLU polymorphisms influences cognitive performance in old age; and (b) if physical activity moderates this effect. Data from the SNAC-K population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 61 publications
7
33
0
Order By: Relevance
“…rs6733839 has stronger effect size (odds ratio of 1.22) compared to other SNPs reported by the meta-analysis, rendering better statistical power for detecting the association. Further, in agreement with our findings, BIN1 was previously shown to be associated with episodic memory performance (in the context of a genotyping pattern involving combination with additional AD genes) (Barral et al, 2012; Ferencz et al, 2014). This is also in line with recent studies reporting BIN1 associations with several cognitive functions in healthy, non-demented elderly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…rs6733839 has stronger effect size (odds ratio of 1.22) compared to other SNPs reported by the meta-analysis, rendering better statistical power for detecting the association. Further, in agreement with our findings, BIN1 was previously shown to be associated with episodic memory performance (in the context of a genotyping pattern involving combination with additional AD genes) (Barral et al, 2012; Ferencz et al, 2014). This is also in line with recent studies reporting BIN1 associations with several cognitive functions in healthy, non-demented elderly.…”
Section: Discussionsupporting
confidence: 92%
“…Episodic memory is highly influenced by genetic contribution (Wilson et al, 2011), and this sub-phenotype is frequently used as primary outcome measure in genetic studies aiming to evaluate the impact of AD related variants on cognitive performance among cognitively normal and impaired populations. Among GWAS confirmed AD risk loci that were associated with this intermediate phenotype are CR1, BIN1, CLU, PICALM , and APOE (Barnes et al, 2013; Barral et al, 2012; Ferencz et al, 2014; Keenan et al, 2012; Sweet et al, 2012). …”
Section: Introductionmentioning
confidence: 91%
“…However, one study reported that older APOE ε4 carriers who are more physically active had higher activity in posterior temporal and parietal regions during an episodic memory task than non-carriers or those with lower physical activity levels. These data suggest that physical activity may circumvent negative effects of carrying a disadvantageous genotype on brain functioning (see also Erickson et al 2013;Ferencz et al 2014). Similar to lifestyle factors, behavior-genetic studies indicate that different diseases may lower resources and make it easier to disclose genetic effects.…”
Section: Factors Affecting Age Magnification Of Genetic Effectsmentioning
confidence: 99%
“…Research on genetic risk approaches have used several procedures for calculating risk scores. For example, prior studies have used an explained variance-weighted genetic risk score [60], an odds ratio weighted risk score [53,54], large number of SNPs to create a polygenic risk score [61,62], weighted sum of the top risk scores [56], and an additive allelic risk score [11,53,63]. …”
Section: Introductionmentioning
confidence: 99%